Effect of the partial substitution of mango and ground chia on the antioxidant capacity in the elaboration of nectar based on sachatomate - Rivera, T. J. C. (2026)
The consumption of products with high nutritional value and antioxidant capacity has increased notably in recent years. Due to health problems such as triglycerides and cardiovascular problems, its use is becoming reduced. So that, chia (Salvia hispánica) and sachatomate (Cyphomandra betacea) have gained interest as an alternative to develop nutraceutical products, compared to conventional products. The objective of the study was to determine the effect of the partial substitution of mango (Mangifera indica) and ground chia (Salvia hispánica) on the antioxidant capacity in the elaboration of nectar based on Sachatomate. The physicochemical characteristics were determined where sample 11 complies with the established parameters: 13.4° Brix, pH 4.323, 0.354 of C6-H8-O7 and viscosity 3967.3 mPas, according to the NTP 203.110 standard. Regarding the antioxidant capacity, sample 12 was the most optimal, according to the DPPH method, it has been determined 104.3 micromoles Trolox equivalents; according to the ABTS method, it was determined with an antioxidant content of 187.4 micromoles Trolox equivalents. Regarding the proximal chemical evaluation, sample 12 was determined to be the most suitable with a moisture percentage of 87.45%, ash 0.32%, crude fiber 0.09%, fat 0.10%, protein 0.45% and carbohydrates 11.59%. Concluding that substituting sachatomate and ground chia significantly influences the antioxidant capacity, increasing to 104.3 and 187.4 micromoles Trolox equivalents, determined by both methods, indicates that nectar consumption can be used to improve the health of consumers.